Coordination Economies - Kyle Bagwell; Garey Ramey (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
This paper considers pricing, cost-reducing investment and dissipative advertising by firms when consumers acquire price information via two information channels, observation of advertising and sequential price search. We find that advertising guides consumers to the lowest prices in the market, even when consumers have the option to search. The threat of search by advertising-uninformed consumers introduces price competition among firms, giving short-and long-run resolutions to the Diamond paradox. Higher concentration raises welfare as a consequence of coordination economies. An extension to loss-leader advertising is developed.
Keywords: 330